(untitled) (Bulletin of Kharkiv National University of Internal Affairs, 2023)
The scientific article defines the methodological aspects of conducting a forensic commodity examination of furniture products, outlines the theoretical and practical problems of commodity research of furniture products, reveals the commodity characteristics of furniture and its defects, and proposes a systematisation of information data on the peculiarities of conducting a forensic commodity examination of furniture products with regard to the characteristic defects of goods. The stages of forensic examination of furniture are presented. The main identification tasks of a commodity expertise are to determine the type, name and assortment group of the product; what materials and components were used in its manufacture; what technology was used to manufacture the furniture product; whether the design parameters and consumer properties of the product under investigation correspond to those stated in the regulatory and technical documentation. The peculiarity of a trade examination of any product is that a defect may arise both through the fault of the manufacturer (seller) and the fault of the buyer (consumer). In practice, there are cases of fraud on the part of companies and individuals, for example, when users intentionally damage parts or components of a product in order to return a product under warranty and receive monetary compensation for an allegedly defective product. This is also relevant for foreign trade agreements, when, by spoiling the delivered goods, the counterparty seeks to receive liquidated damages after termination of the contract, and further, material compensation for lost income according to the arbitration court decision. The article reveals the peculiarities of conducting a forensic commodity examination of furniture products, systematizes the characteristic defects of goods that are most often detected by experts, presents some stages of conducting a forensic commodity examination of furniture. Recommendations regarding furniture quality assessment for participants in external economic activity, expert organizations and consumers are also provided.